(untitled) (Communications in Computational Physics, 2020)
Numerical solution of time-lapse seismic monitoring problems can be challenging due to the presence of finely layered reservoirs. Repetitive wave modeling using fine layered meshes also adds more computational cost. Conventional approaches such as finite difference and finite element methods may be prohibitively expensive if the whole domain is discretized with the cells corresponding to the grid in the reservoir subdomain. A common approach in this case is to use homogenization techniques to upscale properties of subsurface media and assign the background properties to coarser grid; however, inappropriate application of upscaling might result in a distortion of the model, which hinders accurate monitoring of the fluid change in subsurface. In this work, we instead investigate capabilities of a multiscale method that can deal with fine scale heterogeneities of the reservoir layer and more coarsely meshed rock properties in the surrounding domains in the same fashion. To address the 3-D wave problems, we also demonstrate how the multiscale wave modeling technique can detect the changes caused by fluid movement while the hydrocarbon production activity proceeds.